PRIMARY DECOMPOSITION OF A 0-CONNECTED NILPOTENT SPACE (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
It is known that the dierent stages of the Cartan-Whitehead decomposition of a 0-connected space can be obtained as the Adams cocompletions of the space with respect to suitable sets of morphisms. In this note Cartan-Whitehead decomposition is obtained for a nilpotent space, in terms of Adams cocompletion, using the primary homotopy theory developed by Neisendonfer.